LITERATURE REVIEW: ANALYSIS OF THE SYSTEM FOR RECORDING AND REPORTING EXTRAORDINARY EVENTS (KLB) IN HEALTH CARE FACILITIES - Fita Rusdian Ikawati; Achmad Jaelani Rusdi; Elsa Andara Dita Amellia Amellia (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Health service facilities (Fasyankes) play an important role in recording and reporting extraordinary events (KLB) as part of the national health system. However, there are still various obstacles in the recording and reporting system, such as discrepancies in patient identity, data duplication, reporting delays due to manual recording, and lack of digital infrastructure and training of health workers. This study aims to analyze the recording and reporting system of outbreak cases in health facilities based on a literature review of various previous studies. The method used was a literature review by analyzing relevant research results from 2019 to 2024. The results showed that implementing a digital system can improve the accuracy and efficiency of recording and reporting outbreak cases, enable early detection, and accelerate health interventions. However, obstacles such as limited human resources, high workload, and suboptimal coordination between agencies are still a challenge in implementing the system. Therefore, strengthening digital infrastructure, increasing the capacity of health workers, and optimizing coordination between agencies are needed to improve the effectiveness of the outbreak recording and reporting system in health facilities.